School stress in children - Mallett, S. (1997)
Most of us can empathise with feeling stressed. Each of us has our own unique interpretation of what stress is and our own understanding of what stress feels like. We each feel stress from a variety of sources and for a variety of reasons. We all have different coping strategies, which may or may not be effective. It is likely we learned our coping strategies in childhood; children who cope successfully with stress are likely to become adults who cope with stress successfully. Stress is not necessarily a 'bad thing': it can have many positive benefits. But too much stress, or coping ineffectively with repeated stress over long periods of time can have harmful effects on physical and psychological well being. This research investigates stress in school children, focusing specifically on school stress and everyday stressors inherent in schooling. It lets the pupils taking part in the research define their own stress and set the agenda for the research. How the pupils define their stress, their assessment of what is stressful for them in their life at school and how it makes them feel are all accepted unconditionally, and I have endeavoured to be non-judgemental in processing the information about stress disclosed to me by these pupils. The research was conducted over a two year period (1993-1994), at the eleven to sixteen comprehensive school where the author is employed. The data were collected by means of questionnaire, semi-structured interview and pupils' own personal writing and 'stress diaries'. After piloting, the first questionnaire was issued in January 1993 to one hundred and eighty volunteers in every form and every year group in the school (six questionnaires to each of the thirty tutor groups in the school). Of these questionnaires, 167 were returned (92.8%). The questionnaire asked respondents who would be prepared to be interviewed at a later stage, to identify themselves. Forty-five pupils volunteered. From these volunteers I selected pupils who had indicated that they had experienced feeling stress at school at some time on their questionnaire. I tried to keep a balance between males and females wherever possible, and to choose volunteers from across the age range. There were ten male and eleven female interviewees in the final selection one male and one female from year seven; one male and two females from year eight; two males and two females from year nine; and three males and three females from years ten and eleven respectively. The process was repeated again in 1994. Of the one hundred and eighty questionnaires issued in 1994, one hundred and forty three were returned (79%). Possible explanations for the difference in the number of questionnaires returned are discussed in Chapter 6. The same volunteers were interviewed in 1994 as in 1993, with the addition of two new volunteers, one male and one female, from year seven. The questionnaires and interviews were issued and conducted during the same time periods in both years. This was deliberately done to maintain consistency, to confirm the data collected in 1993 and to highlight any periods during the school year when pupils reported feeling more stress than at other times. This was successful as much of the data collected in 1994 does confirm the findings of 1993, and helps to build up a remarkably consistent picture of how pupils perceive stress at school. Originally, the author had planned to repeat the research method for a third year, but it was felt unnecessary to do this due to the corroborative nature of the data already collected. I have presented the results of each year separately rather than amalgamated the two sets of data, not only to emphasise this correlation but also because I wished to present as detailed a picture as possible of the stressful aspects of school life as perceived by the pupils, and although much of it is similar, none of it is the same. Each pupil has offered their own unique interpretation of the stressful school experiences he/she has encountered, and I felt it was important to include them all as equally important and valid in order to preserve the aims and integrity of the research. It would be impossible to amalgamate the data without trivialising the disparity of the experiences being disclosed to me. The main findings of this research suggest that there is a diverse, but ultimately exhaustive, range of school experiences pupils describe as being stressful for them. Most of these experiences can be categorised into domains relating to stressors which are curriculum generated; stressors which are the result of conflict in relationships with peers, teachers and/or family members; everyday life stressors not necessarily associated directly with school and a range of individually unique ‘one off’ stressors ...